Analisis Daya Tampung Jaringan Jalan Tidak Sebidang (Studi Kasus: Flyover Teuku Umar, Kota Bandar Lampung) - Zenia F Saraswati; Balqis Febriyantina Gunari (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The city of Bandar Lampung as the capital of Lampung Province causes a high number of movements so that traffic jams cannot be avoided on several roads in the City of Bandar Lampung. Responding to these problems, the city government of Bandar Lampung has carried out many flyovers as an effort to increase road capacity to meet high demand and is projected to continue to increase. The Teuku Umar flyover in Kedaton sub-district is one of the three flyovers built in 2017-2018. Jalan Teuku Umar has quite a variety of activities, namely the center of trade, education and health activities. This research was conducted to determine the impact caused by the construction of flyovers on traffic performance in both internal and external areas using a VCR projection on the affected roads. This research also considers land use in the vicinity of the projection, which is carried out using the Origin and Destination Matrix data, population projections, vehicle ownership projections, and road capacity. The results of the research analysis explain that the time limit for road services on existing roads / underpasses and flyovers is still stable with a VCR <0.85 is 15 years. However, the condition of the flyover section remains saturated, so the government in 2033 makes it important to limit building intensity.